International Study of the Incidence of Particular Types of Septal Deformities in Chronic Rhinosinusitis Patients: The Outcomes from Five Countries. Issue 5 (September 2014) - Cingi, Cemal; Muluk, Nuray Bayar; Acar, Mustafa; Skitarelić, Neven; Markešić, Josip; Vugrinec, Ozren; Passali, Desiderio; Bellussi, Luisa; Passali, Giulio Cesare; Passali, Francesco Maria; Lopatin, Andrey; Kirdeeva, Alena; et al.
Background: Chronic rhinosinusitis (CRS) may be more frequent in patients with particular types of septal deformities. The aim of this article was to investigate the incidence of particular types of septal deformities in adult CRS patients and healthy volunteers in various countries to determine whether some of them are more frequent in those groups. Methods: This international multicentric study involved 505 subjects from five countries: Croatia, Romania, Italy, Russia, and Turkey. The types of septal deformities were observed and grouped according to the Mladina classification. Subjects were examined by means of native anterior rhinoscopy, anterior rhinoscopy after decongestion, and fiber endoscopy with topical anesthesia. CRS patients have been diagnostically proved by computed tomography scanning of the paranasal sinuses. Results: Considering the CRS patients, the prevalence of so-called vertical deformities (types 2, 3, and 4) was seen. Among them, type 3 deformity was found most frequently in Turkey, Croatia, Italy, and Romania. Conclusion: Type 3 deformity has been found frequently in CRS patients in all five of the countries. Russian subjects exhibited a high frequency of type 4 deformity. Because this type consists of types 2 and 3, the later, again, has been proven to be prevalent in CRS patients also in this group of patients.